Characteristics of Epilepsy Patients in Neurology Outpatient Clinic Siloam Hospitals Lippo Village - Graciela Audrey Dharmawan; Retno Jayantri Ketaren (Universitas Pelita Harapan, 2026)
Introduction: Epilepsy is a chronic neurological disorder affecting approximately 70 million people worldwide. Despite being a treatable condition, many patients in low- and middle-income countries especially Indonesia do not receive adequate Anti-Epileptic Drug (AED) therapy. Previous local studies have reported variations in patient characteristics but often lacked detailed data on epilepsy syndromes and neuroimaging findings. This study aimed to determine the clinical and demographic characteristics of epilepsy patients at the Neurology Outpatient Clinic of Siloam Hospital Lippo Village Methods: This study was a retrospective descriptive cross-sectional study. Secondary data were collected from 111 medical records of epilepsy patients treated at the Neurology Outpatient Clinic between 2022 and 2024. The sampling method used was non-probability convenience sampling. Data were analyzed using univariate statistical analysis, presented as frequencies and percentages. Results: Of the 111 subjects, the majority were adults (69.4%) and male (55.9%). The most common seizure type and epilepsy type were focal seizures (53.2%). The most frequent epilepsy syndrome was temporal lobe syndrome (21.6%), and the most frequent etiology was unknown or idiopathic (64.9%). Monotherapy was the predominant treatment regimen (64.9%), with phenytoin (52.3%) and valproic acid (47.7%) being the most frequently prescribed AEDs. EEG findings were normal in 49.5% of subjects. Among patients with available neuroimaging data, abnormal structural findings were observed more frequently than normal findings (18.0% for CT scan and 21.6% for MRI). Conclusions: The typical patient profile was an adult male with focal epilepsy of unknown etiology receiving monotherapy treatment. Although neuroimaging data were incomplete in many medical records, available results indicated a significant portion of structural abnormalities Keywords: Epilepsy, Characteristics, Anti-epileptic Drugs, Neuroimaging